Resilient Leadership, Institutional Adaptability, and Crisis Communication and Their Role in Emergency Governance in Post-Pandemic Public Administration - Ahmed, Rizwan (Department of Public Administration, Parahyangan Catholic University, 2025)
The COVID-19 crisis laid bare serious gaps in how public agencies handle emergencies, showing that strong leadership, flexible institutions, and clear communication are crucial when faced with emergency situations. This paper looks at those factors together to see how they shape emergency governance in Pakistan, specifically Karachi's public administration after the pandemic. Guided by notions about organizational resilience and adaptive governance, the author used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data from 263 civil servants. Findings show that resilient leaders boost institutional flexibility and clearer messaging, with both improvements feeding into stronger governance. Institutional adaptability also acts as a partial bridge between leadership and overall governance results. Together, the results underline the need to build adaptable processes and open channels, which enable agencies to respond faster and stay accountable in situations of crisis. The study offers new ideas for governance theory and practical tips for officials trying to upgrade preparedness in fast-growing cities. Future work should test the model in other regions and at different levels of government to see how local context changes the story.